Effectiveness of three electronic apex locators to determine root canal working length. - Carolina Campillo-Cortés; Héctor Flores-Reyes; Claudia Dávila-Pérez; Daniel Silva-Herzog; Verónica Méndez-González; Amaury Pozos-Guillén (Journal of Oral Research, 2015)
The aim of this study was to evaluate in vivo the accuracy of three electronic apex locators (EALs) in determining working length (WL) using hand files and a wear technique. Thirty two premolars that were completely formed apically and that were scheduled for extraction for orthodontic reasons from patients between ages of 15 and 20 years old were included. Electronic measurement of WL was performed using the EAL according to the manufacturer’s instructions. The following three EAL were used: A. Root ZX II; B. Raypex 5, and C. Propex II. There were significant difference (p=0.0002) when comparing median differences among the three EAL. Statistical analysis revealed significant differences between Root ZX II vs. Raypex 5 and Root ZX II vs. Propex II (p=0.0044; p=0.0002), while between Raypex 5 and Propex II, there were no statistically significant differences with respect to the accuracy of the EAL in determining WL (p=0.1087). The present findings suggest that Root ZX II presented the highest agreement rate for determining the final WL.